(untitled) (Proceedings of the International Conference on Public Health, 2022)
Indonesia has 31.1% of regencies/cities categorized as low-endemic areas. The areas are expected to accelerate the malaria elimination status; meanwhile, it is crucial to reduce the vector density in the area. Vector data updates in malaria-endemic areas are essential in anticipating the transmission and an increase in malaria cases. The purpose of the study was to get information on new malaria vector updates in low-endemic malaria areas in Indonesia. The study was conducted from 2015-2018 in Jambi, Riau Islands, Special Region of Yogyakarta, Central Kalimantan, North Kalimantan, and South Sulawesi. Mosquito and larva collection was performed in low-endemic areas of malaria. We used the night landing collection, animal-baited trap, livestock bait, light trap, and resting morning collection. The Plasmodium was identified from Anopheles samples using the polymerase chain reaction (PCR) with Plasmodium genus-specific primers. The results showed a new potential vector in low-endemic malaria areas in Indonesia. They are An. vagus (Jambi, Central Kalimantan, South Sulawesi, and Yogyakarta), An. kochi (Jambi), An. dirus and An. barbirostris (Central Kalimantan), and An. subpictus (South Sulawesi). The discovery of the suspected Anopheles species as malaria vectors suggests a potential transmission, and increased cases may occur. Vector surveillance needs to be strengthened to reduce malaria transmission.